A STUDY ON THE INHIBITORY EFFECT OF BINENS BIPINNATA L. EXTRACT ON U14 TUMOUR IN MICE - Zhu, Li-Hong; Qin, Rui-Ying; Guo, Hui-Min; Ding, Xiao-Li; Guan, Xin-Lei; Liu, Shan-Shan; Pan, Ying (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to study the in vitro and in vivo inhibitory effect of Bidens bipinnata L. extract on growth of cervical carcinoma U14 cells. MTT method was used to determine the inhibitory effect of Bidens bipinnata L. extract on U14 tumour cells, and the effects of Bidens bipinnata L. extract on inhibition rate of solid tumour and life prolongation rate of ascites tumour were observed through the establishment of two animal models of mouse cervical carcinoma U14 solid tumour and ascites tumour. In the in vitro MTT assay, the inhibition rate gradually increased with the increase of dose of Bidens bipinnata L. and the extension of time. Its inhibition rate was 70.44% at a concentration of 80μg/L; solid tumour inhibition rates in the high- and low-dose groups and cisplatin group were 49.13%, 2.26% and 75.72% respectively; life prolongation rates in each ascites tumour group were 63.63%, 34.86% and 87.34% respectively. The Bidens bipinnata L. extract has a certain inhibitory effect on growth of mouse cervical carcinoma U14.